ANALISIS SISTEM STRUKTUR GANDA PADA GEDUNG KANTOR DAN GUDANG SUNIA NEGARA DENPASAR - ni komang ayu; Ni Luh Novitasari; Putu Ika Wahyuni (UKI Press, 2024)
Shear walls in a dual system are one of the structural systems to carry most of the lateral load with a maximum percentage of 75%, because geometrically this shear wall structure has greater rigidity so that it will be effective in providing a restraining influence during an earthquake on the building structure. The shear wall used in this building is a rectangular shear wall that is used to support the building structure and to increase the stiffness and stability of the structure against lateral loads. This Office and Warehouse Building has a total height of 16,5 m consisting of 4 floors. The modelling of this building uses ETABS V.17 software with the dimensions of column K1 500 x 500 mm, K2 300 x 300 mm, tie beam S1 300 x 500 mm, S2 300 x 400 mm, beam B1 300 x 500 mm, B2 300 x 400 mm, floor plate 150 mm thick and shear wall 300 mm thick with a span of 3 m. The structure of this building uses reinforced concrete with a concrete quality of 25 Mpa and uses screw reinforcement with a reinforcement quality of fy 420 Mpa. Based on the analysis, the largest inter-floor deviation value for the X direction on the roof slab is 44,3245 mm, while for the Y direction on the 4th floor it is 43,4885 mm. Based on the dual system control requirements, this planning has met the requirements because the percentage of shear walls obtained for the X direction is 72.817% and the Y direction is 74.59%.